IMPLEMENTASI ICE BREAKING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMAN 5 TANJUNG JABUNG TIMUR DALAM MATA PELAJARAN PJOK - Della Amanda sari Sihombing; David Iqroni; Alexander Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in the subject of Physical Education, Sports, and Health (PJOK) in class X at SMAN 5 Tanjung Jabung Timur, which is indicated by low concentration, motivation, and student interest at the beginning of learning, as well as a monotonous learning atmosphere. This study aims to determine the implementation of ice breaking in PJOK learning and its effect on improving student learning outcomes. This research used an experimental method with a one-group pretest–posttest design. The population of this study consisted of all class X students at SMAN 5 Tanjung Jabung Timur, totaling 211 students, with a sample of 109 students from three classes (X-A, X-B, and X-C) selected using random sampling techniques. Data were collected through observation, tests (pretest and posttest), and documentation, then analyzed using normality tests and paired sample t-tests. The results showed that the implementation of ice breaking had a significant effect on improving student learning outcomes, as indicated by an increase in the average score from 62.64 in the pretest to 78.88 in the posttest, with an average gain of 16.24 points. The percentage of students who achieved learning mastery also increased from 11.0% (12 students) to 66.1% (72 students). The paired sample t-test results obtained a t-count value of 30.868 with a significance value of p < 0.001 (p < 0.05), meaning that Hₐ was accepted and H₀ was rejected. Therefore, it can be concluded that the implementation of ice breaking is effective in improving student learning outcomes and creating a PJOK learning atmosphere that is more varied, enjoyable, and less monotonous. Keywords: ice breaking, learning outcomes, PJOK, learning process.